(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Blood pressure is regulated by the renin angiotensin aldosterone system (RAAS). Renin-catalyzed conversion of angiotensinogen to angiotensin I is the rate-limiting step of the RAAS pathway, which arguably makes renin a better target for prevention, treatment and management of hypertension than Angiotensin-Converting Enzyme (ACE). Hydrolysis of food proteins releases bioactive peptides that can interact with receptors, enzymes and molecules in the organism to promote health. Several studies have shown that these bioactive peptides could be exploited for management of hypertension which is a major risk factor for cardiovascular diseases (CVDs). Antihypertensive peptides are bioactive peptides derived from plant and animal sources with inherent potential to ameliorate hypertension by different mechanism including scavenging of free radicals, reduced cholesterol level, inhibit angiotensin-converting enzyme (ACE) activity and renin production. Although there was sufficient information on ACE-inhibitory and antioxidative peptides while information on the potential role of renin-inhibitory peptides against hypertension is limited. Thus, herein the present review primarily used ISI, SCOPUS and PubMed indexed journals containing experimental reports to elucidate the potential role of bioactive peptides against antihypertensive effect via renin inhibition. Key words: Hypertension; Bioactive peptides; Renin inhibition; Mechanism of action.